Climate change adaptation options and their associated costs and benefits in Ireland - Kelly C. De Bruin; Clement Kweku Kyei (The Economic and Social Research Institute (ESRI), 2024)
Climate change poses a significant threat to Ireland, with far-reaching implications for its environment, people, and economy. Consequently, proactive measures are important to mitigate and adapt to these impacts. This paper analyses potential adaptation options and their associated costs and benefits, building upon previous research on the economic implications of climate change in Ireland. We examine the current state of climate change in Ireland, highlighting the various impacts on different sectors. Subsequently, we present an overview of various adaptation measures and their current implementation status. We describe the methodologies used to estimate the costs and benefits of adaptation options, including cost-benefit analysis, cost-effectiveness analysis and multi-criteria analysis. We then estimate the costs and benefits of various adaptation measures in Ireland. Finally, we discuss the barriers to implementing adaptation measures, including financial constraints, policy gaps, and institutional limitations.
Keywords: 330; Klimapolitik; Kosten-Nutzen-Analyse; Policy-Mix; Irland